Differential Games and Oligopoly Theory: An Overview - Luca Lambertini; Roberto Cellini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We illustrate the foundations of the theory of differential games, with particular regard to the definition of information sets and solutions concepts. Then, we provide a survey of several relevant applications of the theory to modelling the behavior of oligopolic firms.
Keywords: 330